2004
DOI: 10.1103/physrevb.69.144301
|View full text |Cite
|
Sign up to set email alerts
|

Vibrational modes in nanocrystalline iron under high pressure

Abstract: The phonon density of states ͑DOS͒ of nanocrystalline 57 Fe was measured using nuclear resonant inelastic x-ray scattering ͑NRIXS͒ at pressures up to 28 GPa in a diamond anvil cell. The nanocrystalline material exhibited an enhancement in its DOS at low energies by a factor of 2.2. This enhancement persisted throughout the entire pressure range, although it was reduced to about 1.7 after decompression. The low-energy regions of the spectra were fitted to the function AE n , giving values of n close to 2 for b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
11
0

Year Published

2005
2005
2018
2018

Publication Types

Select...
5
2
2

Relationship

2
7

Authors

Journals

citations
Cited by 58 publications
(13 citation statements)
references
References 22 publications
2
11
0
Order By: Relevance
“…This remains true as the nanocrystalline material is subjected to pressure, as shown for bcc Fe in Fig. 28 [276]. At pressures of 0.2 and 9.5 GPa both bulk and nanocrystalline samples were bcc, but both had transformed to hcp Fe at the highest pressure of 25-27 GPa.…”
Section: Low-energy Vibrations Of Nanostructuresmentioning
confidence: 73%
See 1 more Smart Citation
“…This remains true as the nanocrystalline material is subjected to pressure, as shown for bcc Fe in Fig. 28 [276]. At pressures of 0.2 and 9.5 GPa both bulk and nanocrystalline samples were bcc, but both had transformed to hcp Fe at the highest pressure of 25-27 GPa.…”
Section: Low-energy Vibrations Of Nanostructuresmentioning
confidence: 73%
“…For nanocrystals, it is generally found that phonon spectral weight is transferred to lower energies, causing an increase in the vibrational entropy as large as 0.2 k B /atom for nanocrystalline materials measured to date [273,275,276,277,285]. Nevertheless, it appears that the entropy of vibrations and configurations is only about half of what is required to give thermodynamic stabilization to a nanocrystalline microstructure at reasonable finite temperatures.…”
Section: Low-energy Vibrations Of Nanostructuresmentioning
confidence: 96%
“…NRIXS signals originate from particular resonant nuclei only, and this complete isotope selec tivity is truly unique among techniques for the study of lattice vibrations. For example, materials surrounding the sample that do not contain resonant nuclei produce no unwanted background, and this feature now permits experiments under extreme pressuretemperature conditions that were impossible before (Lubbers et al, 2000a;Mao et al, 2001Mao et al, , 2004bStruzhkin et al, 2001;Lin et al, 2003Lin et al, , 2004aLin et al, , 2004bLin et al, , 2005bShen et al, 2004;Papandrew et al, 2004;Kobayashi et al, 2004;Zhao et al, 2004). Details on the scattering mechanisms and methodology for NRJXS and SMS have been published elsewhere Sturhahn, 2004).…”
Section: Experimental Methodsmentioning
confidence: 99%
“…The vibrational properties of nanoscrystalline materials (nanocomposites) have been studied extensively experimentally by inelastic neutron scattering and nuclear resonant inelastic X-ray scattering (NRIXS) 9,[32][33][34][35][36][37][38][39][40][41][42] , as well as theoretically 7,8,10,13,[43][44][45][46][47] .…”
Section: Introductionmentioning
confidence: 99%